2020
DOI: 10.1007/s10775-020-09433-4
|View full text |Cite
|
Sign up to set email alerts
|

Using the hope-centered career inventory (HCCI)—Italian version with healthcare professionals

Abstract: To address twenty-first century challenges, Niles, Amundson, and Neault (2011) developed the Hope-Centered Model of Career Development (HCMCD) from which they derived the Hope-Centered Career Inventory (including domains of hope, selfreflection, self-clarity, visioning, goal setting/planning, implementing, and adapting). The current study tests the psychometric properties, structural, convergent, and discriminant validity of the Italian version of the HCCI. Confirmatory factor analyses in a sample of 536 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The HAI has previously been assessed with samples of unemployed job seekers (Amundson et al, 2016;Clarke et al, 2016), individuals in career transition (Niles, Yoon, Balin, et al 2010), university students (Amundson et al, 2013;Yoon et al, 2015), healthcare professionals (Santilli et al, 2020), refugees (Yoon et al, 2019), and individuals with histories of problematic substance use (Currie et al, 2023). Previous research assessing the psychometric properties of the HAI, or its predecessors, have reported good model fit, adequate internal consistency reliability, and supportive evidence for construct validity, including once for problematic substance users (Currie et al,2023;Schreiber et al, 2013;Schindler et al, 2014;Yoon, 2017;Yoon et al, 2015;Yoon et al, 2020).…”
Section: Previous Research On the Hope-action Inventorymentioning
confidence: 99%
“…The HAI has previously been assessed with samples of unemployed job seekers (Amundson et al, 2016;Clarke et al, 2016), individuals in career transition (Niles, Yoon, Balin, et al 2010), university students (Amundson et al, 2013;Yoon et al, 2015), healthcare professionals (Santilli et al, 2020), refugees (Yoon et al, 2019), and individuals with histories of problematic substance use (Currie et al, 2023). Previous research assessing the psychometric properties of the HAI, or its predecessors, have reported good model fit, adequate internal consistency reliability, and supportive evidence for construct validity, including once for problematic substance users (Currie et al,2023;Schreiber et al, 2013;Schindler et al, 2014;Yoon, 2017;Yoon et al, 2015;Yoon et al, 2020).…”
Section: Previous Research On the Hope-action Inventorymentioning
confidence: 99%
“…Reflection further involves individuals having the capacity to examine their thoughts, beliefs, behaviors, circumstances, and emerging self-concepts embedded within their unique life contexts (Niles, Amundson, & Neault, 2010). Regular engagement in self-reflection provides a solid foundation for and increases the probability that new information will be considered in subsequent career planning (Santilli et al, 2021).…”
Section: Reflective Capacity and Hopementioning
confidence: 99%